Efficiency of insulin analogs in young patients with type 1 diabetes mellitus debut during pubertal period - Lyubov' Leonidovna Bolotskaya; Yury Ivanovich Suntsov; Igor Vladislavovich Kazakov; Marina Vladimirovna Shestakova; Ivan Ivanovich Dedov (Сахарный диабет)
Aim. To identify factors responsible for the early development of microvascular complications in patients with type 1 diabetes mellitus (DM1)and to evaluate dependence of their prevalence on the type of insulin. Materials and methods. The study carried out from May 2002 to November 2007 included a random sample of patients with DM1 over 10 years in duration(n=5895, 100%, >=20 years) from the Central, Volga, Ural, Siberian, North-West and Southern federal districts. All patients underwentexamination of eye fundus and feet, measurement of microalbuminuria, creatinine, urea, serum lipid spectrum and HbА1с. Results. Mean HbА1с level in patients of group 1 (using insulin analogs) was significantly lower than in group 2 (using homan insulin) (Me 8,5?0,2%;9,7?0,4% SD* respectively) p>0,01. Mean daily insulin dose in group 1 and 2 was >1,0 and